Drawing on animal hide by George Twok Aden Ahgupuk, ca. 1930-1950 (1930)
George Twok Aden Ahgupuk (1911-2001) was an Inupiat native artist from Shishmaref, Alaska, whose work depicted village life, hunting of seals, walrus, whale, and polar bears, and Alaska wildlife and scenery, similar to what is featured in this piece. Twok developed his own technique for bleaching caribou, reindeer, and moose hides, and he shared this technique with no one. This work was collected by Fred Lewis who, in the 1930s, sailed his Seattle-built steam yacht, "Stranger," to Alaska, where he visited numerous settlements and collected hundreds of pieces of traditional and "market" art - items made by Alaskan natives for sale to non-natives. Thanks to the Lewis family, MOHAI has one of the larger collections of early 20th century Alaskan market art in the Seattle area. 1 Drawing; Materials: Pen --ink --leather --wood; Dimensions: 19 in.H x 37 in.W